2002
DOI: 10.1017/s0031182002001786
|View full text |Cite
|
Sign up to set email alerts
|

A multiplex allele specific polymerase chain reaction (MAS-PCR) on the dihydrofolate reductase gene for the detection of Cryptosporidium parvum genotypes 1 and 2

Abstract: (Received 11 September 2001 ; revised 11 January 2002 ; accepted 4 February 2002)  A multiplex allele specific polymerase chain reaction (MAS-PCR) based on the Cryptosporidium parvum dihydrofolate reductase (dhfr) gene sequence differentiates genotype 1 (' Human ') from 2 (' Cattle ') in a 1-step reaction. The MAS-PCR was validated on a panel of 34 microscopically positive C. parvum faecal samples of human and animal origin in comparison with 2 published PCR-restriction fragment length polymorphism (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…A TaqMan PCR assay targeting the 18S ribosomal DNA (rDNA) has allowed sensitive detection of Cryptosporidium species (155). Various other PCR assays for the detection of Cryptosporidium species in stool specimens have also been developed (18,107,136,293). While being more expensive and time-consuming, PCR and ELISA have shown superior sensitivity for the detection of Cryptosporidium species compared to conventional staining and microscopy (158,199).…”
Section: Cryptosporidiummentioning
confidence: 99%
“…A TaqMan PCR assay targeting the 18S ribosomal DNA (rDNA) has allowed sensitive detection of Cryptosporidium species (155). Various other PCR assays for the detection of Cryptosporidium species in stool specimens have also been developed (18,107,136,293). While being more expensive and time-consuming, PCR and ELISA have shown superior sensitivity for the detection of Cryptosporidium species compared to conventional staining and microscopy (158,199).…”
Section: Cryptosporidiummentioning
confidence: 99%
“…In immunosuppressed patients, the disease is often more severe, is usually associated with chronic diarrhea and wasting, and can be life threatening (1). Laboratory diagnosis of cryptosporidiosis traditionally relies on special staining techniques, while alternative diagnostic techniques have also been employed, including ELISA and various PCR assays (2,9,12,32). A number of studies have demonstrated that PCR has superior sensitivity for the detection of Cryptosporidium species compared to conventional staining, microscopy, and ELISA (14,16).…”
mentioning
confidence: 99%
“…One portion in a 15ml Falcon tube was stained with Lugol's iodine. Smear preparation of the other portion on clean dry 76mm x 26mm microscopy slide was stained with the modified Ziehl-Neelsen stain (23) .…”
Section: Sample Processingmentioning
confidence: 99%
“…The assay was performed on species-specific DNA controls and a range of well-defined stools samples, and it achieved 100 percent specificity and sensitivity. The use of this assay in a diagnostic laboratory would provide sensitive and specific diagnosis of the main parasitic infections and could improve patient management and infection control (23) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation